A Static Synchronous Compensator for Displacement Power Factor Correction under Distorted Mains Voltage Conditions - Cimbals, R.; Krievs, O.; Ribickis, L. (Elektronika ir Elektrotechnika, 2011)
A STATCOM system is presented in this paper applied for compensation of displacement power factor under distorted mains voltage conditions. The developed STATCOM control system consists of two regulating loops - DC link voltage control loop with anti-windup PI controller and the current control loop with a feed-forward PI controller. The simulation results indicate that the developed control system performs well, ensuring displacement power factor compensation with good transient and steady state performance even under significantly distorted grid voltage conditions. Ill. 15, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.291